1995
DOI: 10.7326/0003-4819-123-11-199512010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Colitis: An Efficient Clinical Approach to Diagnosis

Abstract: Clinicians at the bedside can use readily available clinical and laboratory information to decide which patients are likely to have C. difficile disease and when it is appropriate and useful to order specific diagnostic tests for C. difficile toxin. Such data are also useful in determining the number of stool samples that reasonably excludes the diagnosis of C. difficile colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
1
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(85 citation statements)
references
References 0 publications
3
77
1
4
Order By: Relevance
“…14,17,[21][22][23][24] Although our local experience revealed cephalosporin use to be predictive of cytotoxin results in both the validation and derivation sets, others have demonstrated associations for different classes of antibiotics, [25][26][27] and have shown reduced rates of C. diffi- cile-associated disease when the usage of these antibiotics was restricted. 28 Thus, to enhance the generalizability of our models to other hospital settings, we did not present models including specific antibiotic variables (e.g., prior cephalosporin use) in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,17,[21][22][23][24] Although our local experience revealed cephalosporin use to be predictive of cytotoxin results in both the validation and derivation sets, others have demonstrated associations for different classes of antibiotics, [25][26][27] and have shown reduced rates of C. diffi- cile-associated disease when the usage of these antibiotics was restricted. 28 Thus, to enhance the generalizability of our models to other hospital settings, we did not present models including specific antibiotic variables (e.g., prior cephalosporin use) in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…20 In a recent study, Manabe et al reported that cephalosporin use, the presence of semiformed stool, and the presence of fecal leukocytes were independently predictive of C. difficile toxin results. 14 Our study has the important advantage that it used clinical criteria alone to define a patient subgroup at very low risk of C. difficile-associated disease. Using clinical data alone is much more practical and economical than using one or more laboratory tests to decide whether or not to perform others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a general population, certain symptoms and historical features have been identified to predict the individuals at highest risk for C. difficile infection. Besides the commonly recognized risk factors for C. difficile infection (antibiotic use and hospitalization) (8), the presence of fecal leukocytes and the presence of semiformed stool were identified as important predictors in a previous study (9). However, the utility of clinical findings and appropriate history is limited in IBD.…”
Section: Ajg -September 2001mentioning
confidence: 99%
“…При лихорадке, нарастании лейкоцитоза в крови, появления лейкоцитов в кале нужно запо-дозрить ПМК, при котором, несмотря на прекращение антибио-тикотерапии, в большинстве случаев частота стула растет, появ-ляются дегидратация и гипопротеинемия. В тяжелых случаях ПМК быстро наступает обезвоживание, развиваются токсиче-ское расширение и перфорация толстой кишки, возможен ле-тальный исход [23][24][25].…”
unclassified